CONNECTIVITY OF BIVALVES BETWEEN MANGROVE AND SEAGRASS ECOSYSTEMS IN KELAPA DUA ISLANDS: KONEKTIVITAS BIVALVIA ANTARA EKOSISTEM MANGROVE DAN LAMUN DI PULAU KELAPA DUA - Srimariana, Endang Sunarwati; Ningtyas, Azizah Lutfia; Lestari, Dea Fauzia; Subhan, Beginer; Zamani, Neviaty Putri; Sidabutar, Tumpak (Jurnal Teknologi Perikanan dan Kelautan, 2025)
Kelapa Dua Island, part of the Seribu Islands, is rich in biodiversity within the mangrove and seagrass ecosystems. Bivalves serve as bioindicators, crucial for assessing the health of these ecosystems. This study aimed to analyze differences in bivalve diversity between mangrove and seagrass environments and examine their associations between and within these habitats. Data were collected through mangrove and seagrass density surveys, water quality measurements, and sediment analysis. Line transect and plot methods were used for mangrove observation, while the Seagrass Watch method was applied for seagrass observation. Bivalve samples were collected using PVC pipes (up to a depth of 10 cm) for subsurface individuals and visual surveys for exposed species. The island’s sandy substrate supported a variety of bivalve species. Fifteen bivalve species from six families were identified: Tellinidae, Cardiidae, Veneridae, Lucinidae, Donacidae, and Pinnidae. Bivalve density was significantly higher in the seagrass ecosystem (1,029 ind./100 m²) compared to the mangrove ecosystem (366 ind./100 m²), with the family Tellinidae showing the highest density (664 ind./100 m²). Ecological indices indicated stable conditions, with a diverse and evenly distributed bivalve community, reflecting a healthy environment. Correspondence analysis revealed that bivalve species were more concentrated in stations representing seagrass ecosystems, highlighting a stronger association with seagrass habitats.